PROFIL PEMAHAMAN KONSEP FUNGSI KUADRAT OLEH SISWA KELAS IX A SMP NEGERI 2 BANAWA DITINJAU DARI KEMAMPUAN MATEMATIKA - Muhammad Muazin; Baharuddin Paloloang; Pathuddin Pathuddin (Universitas Tadulako, 2025)
The purpose of this study was to obtain a description of the understanding of the concept of quadratic function by high, medium, and low mathematics ability students of class IX A SMP Negeri 2 Banawa. This type of research is qualitative research. The subjects in this study were three students of class IX A SMP Negeri 2 Banawa in the odd semester of the 2022/2023 academic year consisting of one student each with high, medium, and low mathematics abilities. Data collection techniques used written assignments and interviews. The results of this study indicate that (1) high mathematics ability students can restate concepts that have been learned, identify examples and not examples, and classify objects according to certain properties in accordance with the concept; (a) present concepts and (b) apply or apply concepts algorithmically, (2) medium mathematics ability students can restate concepts that have been learned, identify examples and not examples, and classify objects according to certain properties according to their concepts; (a) present concepts, (3) low mathematics ability students can restate concepts that have been learned, identify examples and not examples.